A New Expanded Mixed Element Method for Convection-Dominated Sobolev Equation - Jinfeng Wang; Yang Liu; Hong Li; Zhichao Fang (The Scientific World Journal)
We propose and analyze a new expanded mixed element method, whose gradient belongs to the simple square integrable space instead of the classical H(div; Ω) space of Chen’s expanded mixed element method. We study the new expanded mixed element method for convection-dominated Sobolev equation, prove the existence and uniqueness for finite element solution, and introduce a new expanded mixed projection. We derive the optimal a priori error estimates in L2-norm for the scalar unknown u and a priori error estimates in (L2)2-norm for its gradient λ and its flux σ. Moreover, we obtain the optimal a priori error estimates in H1-norm for the scalar unknown u. Finally, we obtained some numerical results to illustrate efficiency of the new method.